Accuracy and Delay of Using Ultrasound in Testicular Torsion - Michael Chen; Rachel Esler (Journal of Urological Surgery, 2019)

(untitled)
Objective:Testicular torsion is an emergency which can result in testicular loss. Ultrasounds are controversial due to the delay in time to theatre. Our study aimed to quantify the delays in time to theatre as well as review the correlation between ultrasound and operative findings across the literature. We also review the practice of orchidopexy when testicular torsion was not found.Materials and Methods:Two years of scrotal explorations were retrospectively reviewed based on electronic medical records. Differences in the time to theatre were calculated using a two-sample t-test. A review of studies analyzing the accuracy of ultrasound in torsion was conducted.Results:Of the 41 patients included, 10 patients (24.3%) had testicular torsion. Seventeen patients (41%) had an ultrasound prior to surgery which resulted in a mean delay of 3 hours and 30 minutes. Our data showed a sensitivity of 100% and specificity of 92%. A combination of our data with the literature gives a sensitivity of 91.9% (n=124/135) and specificity of 98.9% (n=848/870). In those without torsion, 5 (16%) patients had no orchidopexy performed, 13 (42%) had unilateral orchidopexy and 13 (42%) had bilateral orchidopexy performed.Conclusion:Ultrasound causes significant delays in scrotal exploration which increases the risk of testicular loss. However, despite criticism of its accuracy, ultrasound appears to be highly accurate in the literature and has its use if there is clinical uncertainty. Long-term data is lacking on performing orchidopexy if torsion is not present and clinical practice continues to vary in this area.